ELECTROCHEMICAL DEGRADATION OF CHLORPYRIFOS IN AQUEOUS SOLUTIONS USING G/NB2O5 AND NB/NB2O5 ELECTRODES - NASSER M. ABU GHALWA (International Journal of Pharma and Bio Sciences, 2013)
Glass/Nb2O5 and Nb/Nb2O5 electrodes were prepared by electrodeposition and used as anodes for electrochemical degradation of chlorpyrifos (CPF) in aqueous solution. Different operating conditions and factors affecting the treatment process including current density, temperature, initial concentration of chlorpyrifos, pH, conductive electrolyte and time of electrolysis were studied and optimized. The best degradation occurred in the presence of NaCl (1gL-1) as conductive electrolyte. After 30 min, nearly complete degradation of chlorpyrifos was achieved (94% and 82%) using G/Nb2O5 and Nb/Nb2O5 electrodes at pH 10.8. Higher degradation efficiency was obtained at room temperature (20-30oC). The optimum current density for the degradation of chlorpyrifos on both electrodes was (25 mAcm-2).